Determinación de procesos de Dirección de Posgrado y Educación Continua que integran el sistema de gestión de organización educativa - ESPAM MFL - Macías Vélez, Samia Jamileth (2024)
This research was conducted with the sole objective of determining the Postgraduate and Continuing Education Management Processes that are part of the Educational Organization Management System at ESPAM MFL. The study was carried out in three stages, directly related to the specific objectives of the research. First, the current situation of the Postgraduate and Continuing Education Management processes was diagnosed, through the preparation and execution of an interview that provided valuable information for the study. Next, the processes that make up the institution's Educational Organization System were identified. The final stage involved developing a proposal to update the existing processes of the Postgraduate and Continuing Education Management, integrating them into the process manual as part of the Quality Management System through flowcharts to address the deficiencies found. Various research methods were applied, such as deductive, inductive, synthetic-analytic approaches, along with different types, techniques, and tools of investigation. The results indicated shortcomings in the processes mentioned earlier at ESPAM MFL, identified through the implementation of field instruments. In conclusion, this study highlights the importance of establishing and evaluating processes in a responsible and efficient manner to improve and strengthen them within the institution, ensuring the effective development of their performance.